oPloP Pola Asuh Keluarga yang Memiliki Anak Menikah Dini di Desa Legok Kecamatan Lohbener Kabupaten Indramayu - Sabrina, Amelia Tri; Susilowati, Ellya; Nainggolan, Atirista (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
Upbringing is the way families interact with children consistently over time. In applying parenting, parents often have limitations in providing it which causes negative impacts on children such as falling into early marriage. In Legok Village, which still has a society that still holds firm to traditional and religious values, parents apply upbringing by approving their children to practice early marriage on the grounds that they want to avoid children from committing adultery. This study aims to obtain an empirical description of the characteristics of informants, the application of aspects of control, communication, and family assistance to children. This research design is qualitative research with the type of intrinsic case study and the determination of informants through the purposive method. The main informants in this study are four parents from families who have early married children and early married children. Data collection techniques were conducted using in-depth interviews, observation, and documentation studies. The results showed that the application of control, communication, and mentoring is still not optimal because parents are busy working outside the home until late at night so they do not have enough time to supervise and assist children in carrying out their daily lives. Based on these issues, researchers propose a program to address the problem at hand asa preventive measure to reduce the number of premature marriages and the risk involved in early marriage, which is